(untitled) - Jacobs, Francis G. (Oxford, 1996)
The book addresses a wide range of human rights: from a prohibition on torture to the treatment of transsexuals. The system for the protection of these rights under the Convention represents the most complete judicial model for protecting such rights.
Keywords: Civil rights,Human rights; Europe